Prevalence Of Childhood Obesity Among School Going Children and Its Associated Socio-Demographic Factors in Shirur Village, Bagalkot - Pavan S Kalasker; Arshiya Tarannum (Medsci Publications, 2016)
Introduction: The rise non-communicable diseases in India is not restricted to urban localities but fast spreading to rural areas. Objectives: The study was conducted to assess prevalence of obesity among school going children and to find correlation of various socio-demographic factors affecting obesity in children in this area. Methodology: An institution based cross-sectional study was conducted among 1308 in rural schools. Students were interviewed and height and weight were recorded. Results: The prevalence of overweight and obesity was 2.52% and 0.99% among school children. Prevalence of overweight was significantly high in children studying in middle school (5th, 6th and 7th standard), private schools, literacy level of mother more than SSLC, father having occupation in the category employed or own business and not participating in outdoor games. Prevalence of obesity was significantly high in female gender, children with father having occupation in the category employed and those participating in sedentary activities like TV watching, mobile phones etc. for more than one hour per day. Conclusion: Decreased outdoor playing, increased sedentary activities like TV watching and mobile phone usage among school children are important risk factors for childhood obesity.